MBNL1-AS1 Promotes Hypoxia-Induced Myocardial Infarction via the miR-132-3p/RAB14/CAMTA1 Axis. (4th February 2023) - Li, Yanbing; Zong, Min; Guan, Xiaonan; Wu, Xuejiao; Ma, Guiling; Wei, Yu; Li, Zhi
Abstract : Background. Mounting evidence have indicated that long noncoding RNA (lncRNA) muscleblind like splicing regulator 1 antisense RNA 1 (MBNL1-AS1) play a crucial regulatory role in cardiovascular disease, myocardial infarction (MI) included. In this research, we sought to probe into the biological function and potential mechanism of MBNL1-AS1 in MI. Methods. Cardiomyocytes were treated under hypoxic conditions for 0–12 h. Functional assays including CCK-8 and flow cytometry were performed to assess hypoxia-stimulated cardiomyocyte viability and apoptosis, respectively. Moreover, bioinformatics analysis and mechanical assays were conducted to reveal the competitive endogenous RNA (ceRNA) mechanism of MBNL1-AS1. Results. The upregulation of MBNL1-AS1 was found in hypoxia-stimulated cardiomyocytes. Functionally, the downregulation of MBNL1-AS1 dramatically promoted hypoxia-induced cardiomyocyte viability and inhibited apoptosis. Mechanistically, miR-132-3p bound to MBNL1-AS1 in hypoxia-induced cardiomyocytes, and miR-132-3p directly targeted RAB14, member RAS oncogene family (RAB14) and calmodulin binding transcription activator 1 (CAMTA1). Furthermore, MBNL1-AS1 upregulates the expression of RAB14 and CAMTA1 in hypoxia-stimulated cardiomyocytes via targeting miR-132-3p. Conclusions. The current study revealed the critical role of the MBNL1-AS1/miR-132-3p/RAB14/CAMTA1 axis in MI, indicating MBNL1-AS1 as an innovative therapeutic target for MI.